Sky high [videorecording (Blu-Ray)] - Mitchell, Mike (Director); Russell, Kurt; Preston, Kelly; Angarano, Michael; Gunn, Andrew, 1969-; Hernandez, Paul; Schooley, Bob; McCorkle, Mark; Panabaker, Danielle; Winstead, Mary Elizabeth (Walt Disney Home Entertainment : Distr. by Buena Vista Home Entertainment, 2006)
When you're the son of the world's most legendary superheroes there's only one school for you - Sky High, an elite high school that molds today's power-gifted students into tomorrow's superheroes. The problem is that Will Stronghold has no superpowers!